Calopogonium caeruleum- An alternate cover crop in rubber plantations - Philip, A; Jessy, M.D (Rubber Science, 35(1): 72-77., 2022)
Conserving soil and sustaining/improving soil fertility are important in agriculture and maintaining a ground cover is one of the most effective and cheapest means for this purpose. Performance of a shade tolerant cover crop, Calopogonium caeruleum (C. caeruleum) in rubber plantation was evaluated by establishing it in the initial (1-4 years) and later immaturity (5-7 years) phase (after pineapple intercropping) of rubber at different locations in Kerala. In the trials during the initial phase, the performance of C. caeruleum was compared with that of Mucuna bracteata (M. bracteata), which is a common shade tolerant cover crop in rubber plantations and it was found that growth of C. caeruleum was less Nitrogen (N) Nutrient accumulation in the 2 1/2 year old C. caeruleum was 71-76.6, 4.5-6.5, 47.5-60.5, 23.4-48.4 and 7.2-7.8 kg ha-1 of N, P, K, Ca and Mg, respectively. The trial on feasibility of establishing C. caeruleum under partial shade, after the removal of pineapple intercrop showed that even though the growth of C. caeruleum was slow initially, it established well in the plantation in the later phase. Dry matter production of 31/2 year old C. caeruleum under partial shade was four t ha-1 and nutrient accumulation was 107.85, 10.25, 79.54, 44.31 and 5.78 kg ha-1 of N, P, K, Ca and Mg, respectively. An improvement in soil properties and soil moisture was observed after the establishment of C. caeruleum. Soil pH also increased in the C. caeruleum established field. Unlike Mucuna, flowering and seed set were noticed in C. caeruleum in Kerala. It also survived in the field during summer.
Keywords: Calopogonium caeruleum; Cover crop; Partial shade; Rubber plantation